The quality and value of sudden infant death necropsy reporting in Ireland. Issue 10 (26th September 2003) - Sheehan, K M; McDonnell, M; Doyle, E M; Matthews, T; Devaney, D M
Abstract : Background: Infant necropsies are important for identifying cause of death. Recently issued guidelines have recommended investigations to be performed following sudden unexpected death in infants. Aims: To evaluate the quality and value of infant postmortem reporting. Methods: Postmortem reports from 1994–1996 and 1998–2000 in Ireland were evaluated using the National Sudden Infant Death Register. Scoring was by a modification of the Rushton system based on the extent of the postmortem data. The finding of additional pathological information was also assessed. Results: Of the 274 cases registered during the selection period, reports were available for 245. Overall quality of necropsy reporting was below the minimum accepted standard in 55.5%; 47% of the necropsies were performed in regional paediatric pathology centres. The quality of necropsies performed in regional centres was significantly higher than those performed elsewhere. Although 86% of the cases were defined as sudden infant death syndrome (SIDS; no cause of death found), the finding of additional pathological information was significantly related to the extent of the necropsy. There was a significant improvement in the quality of necropsies after the postmortem guidelines were issued. Conclusions: The overall quality of sudden unexpected infant death necropsies in Ireland is less than adequate. A minimum accepted standard of necropsy is required before a diagnosis of SIDS can be made. Although standards have improved recently, this study highlights the need to adhere to published guidelines and the importance of auditing the effect of introducing practice guidelines on clinical practice to complete the audit loop.